CORRELATION OF WIDAL TITER WITH THE NUMBER OF LEUKOCYTES, LYMPHOCYTES AND NEUTROPHILS IN TYPHOID FEVER PATIENTS - Desi Fitriani; Andika Aliviameita (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2026)
Background: Typhoid fever is an acute infection caused by the bacteria Salmonella typhi. In typhoid fever patients, abnormal leukocyte, lymphocyte, and neutrophil counts are often found. Typhoid fever is prevalent in tropical regions, including Indonesia, where it ranks fifth among infectious diseases, affecting 1.6% of the general population. Objective: The aim of this study is to determine the correlation between Widal titer and the number of leukocytes, lymphocytes, and neutrophils in typhoid fever patients. Methods: The research design used quantitative analysis with a cross-sectional method. The study utilized secondary data from 30 respondents patients with typhoid fever at ‘Aisyiyah Siti Fatimah Tulangan Hospital, conducted in April 2024. Results: The research data were analyzed using Spearman's correlation test in SPSS, and the results showed a significant correlation (p=0.014; r=-0.444) between the Widal titer for S. typhi O and S. typhi H with the leukocyte count, no significant correlation (p=0.855; r=0.035) between Widal titers for S. typhi O and S. typhi H with lymphocyte counts, and a significant correlation (p=0.023; r=-0.413) between Widal titers for S. typhi O and S. typhi H with neutrophil counts. Conclusion: Based on the research results, here is a significant correlation between Widal titer and leukocyte count and between Widal titer and neutrophils. There is no significant relationship between Widal titer and lymphocyte count in patients with typhoid fever.